Single-cell analysis uncovers clonal acinar cell heterogeneity in the adult pancreas - Wollny, Damian; Ziebell, Frederik; Marciniak-Czochra, Anna (Developmental cell, 2016)
Acinar cells make up the majority of all cells in the pancreas, yet the source of new acinar cells during homeostasis remains unknown. Using multicolor lineage-tracing and organoid-formation assays, we identified the presence of a progenitor-like acinar cell subpopulation. These cells have long-term self-renewal capacity, albeit in a unipotent fashion. We further demonstrate that binuclear acinar cells are terminally differentiated acinar cells. Transcriptome analysis of single acinar cells revealed the existence of a minor population of cells expressing progenitor markers. Interestingly, a gain of the identified markers accompanied by a transient gain of proliferation was observed following chemically induced pancreatitis. Altogether, our study identifies a functionally and molecularly distinct acinar subpopulation and thus transforms our understanding of the acinar cell compartment as a pool of equipotent secretory cells.